RASIO MONOSIT LIMFOSIT SEBAGAI PREDIKTOR KEPARAHAN NEFROPATI DIABETIK PADA PASIEN DIABETES MELITUS TIPE 2 - Bernando, Andri; Siregar, Jelita; Syafril, Santi (Universitas Prima Indonesia, 2023)
Diabetic nephropathy is a complication that often occurs in diabetics. In this disease, there is damage to the kidney filter, known as the glomerulus. Due to glomerular damage, diabetic nephropathy is closely related to the mechanism of inflammation. The Monocyte-Lymphocyte Ratio is a relatively new marker of inflammation. This study aims to explore the significance of the prediction of the Monocyte-Lymphocyte Ratio as a predictor of the severity of diabetic nephropathy in Type 2 Diabetes Mellitus (DMT2) patients at H. Adam Malik Hospital, Medan. The research was conducted using the cross-section method. This study took blood samples from 44 patients with type 2 diabetes mellitus with diabetic nephropathy, 22 patients with macroalbuminuria, and 22 patients with microalbuminuria. Then blood was drawn from the vein, and the Monocyte-Lymphocyte Ratio was assessed in all patients. In this study, the average MLR for all patients was 0.41±0.037. There was a significant difference between MLR values ​​in diabetic nephropathy patients with macroalbuminuria compared to diabetic nephropathy patients with microalbuminuria (p<0.001). The optimal cut-off value of MLR in predicting diabetic nephropathy with macroalbuminuria and microalbuminuria was 0.37 with a specificity of 81.8% and a sensitivity of 81.8%. The MLR value in type 2 diabetic patients with diabetic nephropathy can be used as a prognostic factor for the incidence of microalbuminuria and macroalbuminuria.